Users' satisfaction levels about mHealth applications in post-Covid-19 times in Saudi Arabia. - Turki M Alanzi (PLoS ONE, 2022)
Purpose This study aims to investigate the users' satisfaction levels about mHealth applications and their intentions to use them in future (in post-Covid-19 times) in Saudi Arabia. Methods A cross-sectional survey design was adopted in this study. The mHealth App Usability Questionnaire (MAUQ)22 was used in this study. An online version of the survey was created using Google Surveys, and a link for the survey was generated. As the objective of this study is to assess the users' satisfaction levels about mHealth applications and their intentions to use them in future (in post-Covid-19 times) in Saudi Arabia, all individuals who used or using mHealth applications will be included in this study. At the end of the survey time period, 318 responses were received. Results Items including 'easy to learn using the app' (mean rating = 3.9), 'easy to find information on the application'(mean rating = 3.9), 'interface of the app' (mean rating = 3.8) were rated to be highly effective by the participants.). However, ability to recover from mistakes while using the applications (mean rating = 2.9), inconsistency in navigation (mean rating = 2.9), and lack of all necessary functions (mean rating = 2.3) were few issues identified. No statistically significant difference of opinions was observed in relation to all sub-scales of usability factor. Conclusion Although the satisfaction levels are good with respect to mHealth applications, the sudden rise in the mHealth users can be partly linked to the several psychological issues such as anxiety and depression among people and also because of restricted access during the pandemic.